2020
DOI: 10.26905/jrei.v1i2.5436
|View full text |Cite
|
Sign up to set email alerts
|

Tendensi Forward Looking Behavior Dalam Kredibilitas Bank Indonesia

Abstract: Tujuan dari penelitian ini adalah untuk menyelidiki perilaku kebijakan moneter di Indonesia,melalui variabel kredibilitas Bank Indonesia. Penelitian ini dilakukan di Bank Sentral Indonesiakarena data sekunder diambil dari Bank Sentral Indonesia, dengan sebagian diperoleh dari BiroPusat Statistik (BPS), dan World Economic Outlook IMF (Dana Moneter Internasional). Datayang dikumpulkan dalam penelitian ini adalah sekunder, yang diterbitkan secara resmi oleh BankSentral Indonesia, Dana Moneter Internasional (IMF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The VAR test is conducted through a series of stages. Initially, a Granger causality test is performed to examine the presence of reciprocal relationships among the variables in the model [30]. Subsequently, a cointegration test, specifically the Johansen Cointegration Test, is conducted to determine whether the variables in the model are integrated or not.…”
Section: Historical Variance Decompositionmentioning
confidence: 99%
“…The VAR test is conducted through a series of stages. Initially, a Granger causality test is performed to examine the presence of reciprocal relationships among the variables in the model [30]. Subsequently, a cointegration test, specifically the Johansen Cointegration Test, is conducted to determine whether the variables in the model are integrated or not.…”
Section: Historical Variance Decompositionmentioning
confidence: 99%
“…Stabilitas moneter dalam negeri, khususnya Indonesia, tentu sama pentingnya dengan stabilitas variabel makroekonomi fiskal yang lain, karena kredibilitas bank sentral dalam pengendalian inflasi pada negara dengan ekspektasi perilaku forward looking sangat menentukan arah perekonomian ke depan. Kredibilitas moneter tidak hanya tentang pengendalian oleh bank sentral, tetapi juga untuk mengeliminasi trade off negatif antara banyak variabel makroekonomi lainnya, seperti kesenjangan output dan nilai tukar (Waluyo, et al, 2011;Suwondo, et al, 2020).…”
Section: Spillover Effect As Pada Variabel Makroekonomiunclassified
“…Financial literacy in Indonesian society is now at a low level. Low financial literacy can be caused by the ability to make the wrong financial plans, which causes bias [9]. People cannot achieve prosperity at the right age and then continue to decline when they enter an age that is no longer productive.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that financial literacy can be promoted by developing suitable financial attitudes related to risk tolerance, education, and time perspective [15]. The financial attitudes of SME managers impact their ability to obtain financing and expand capital, as well as other business operations [16]. He stated that successful individuals possess financial acumen, enabling them to maintain long-term savings and futureoriented investments.…”
Section: Introductionmentioning
confidence: 99%